Pengaruh Perubahan Lingkungan Bisnis terhadap Adaptasi Perilaku Pedagang Pasar Karangpandan Karanganyar di Jawa Tengah - Danang Sunyoto; Magister Alfatah Kalijaga; Melniya Rahma Sari (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Objectives–To analyze the influence of changes in the business environment on the behavioral adaptation of traders at Karangpandan Market, Karanganyar in Central Java. Design/Methodology/Approach–The study used a sample of traders at Karangpandan Market, Karanganjar in Central Java. Data collection methods were questionnaires and observations. Data analysis methods used qualitative descriptive and quantitative. Research Results–A total of 110 market traders were dominated by female traders, 80 of whom were 73%, aged 31-40 years (41%), with a business period of 11-15 years (42%). The business environment has a positive and significant effect on the behavioral adaptation of traders at Karangpandan Market, Karanganyar in Central Java.